Analyzing Students’ Discrimination in Primary School - Analisa Listanti; Sri Harmianto; Sriyanto Sriyanto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
The negative stigma which causes discrimination appears because of someone’s point of view towards the diversity of race, religion, social, or culture. This diversity can also be found in primary school. Some student are not able yet to appreciate and respect the diversity. This research used a qualitative approach with study case method of giving the knowledge about discrimination in primary school. This research aimed to find out the cause, effect, and effort in minimizing discrimination at school. Based on the data obatained, the causing factors of the discrimination are social background, physical disability, and strong and weak groups at school. Forming the attitude to appreciate and respect diversity on students can be achieved through daily leraning activity at school which can be created through multicultural education approach in order to minimize discrimination in primary school. Keywords: Discrimination, Case Study, Multicultural Education.